PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Diphayana, Wahono; Kurniawan, Kurniawan (LPPM Universitas Nias Raya, 2023)
This research was conducted with the aim of finding out whether there is an effect of capital structure, company size and investment decisions on the value of companies engaged in the pharmaceutical sector listed on the IDX for the period 2018 – 2020. Where researchers processed data using the SPSS Version 24 application. The processing results were obtained data where capital structure has an effect on firm value while company size and investment decisions have no effect on firm value.